2015
DOI: 10.1002/jmri.25050
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pulmonary embolism with free-breathing dynamic contrast-enhanced MRI

Abstract: Free-breathing DCE MRI may have potential use for the assessment of PE, and does not require patient cooperation in breath-holding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In addition to that, free‐breathing techniques are desirable in patients with impaired lung function. Recently, the feasibility of DCE‐MRI in free breathing was demonstrated in healthy volunteers and patients with acute pulmonary embolism . Although these results are promising, DCE‐MRI is performed with a breath‐hold at most sites.…”
mentioning
confidence: 99%
“…In addition to that, free‐breathing techniques are desirable in patients with impaired lung function. Recently, the feasibility of DCE‐MRI in free breathing was demonstrated in healthy volunteers and patients with acute pulmonary embolism . Although these results are promising, DCE‐MRI is performed with a breath‐hold at most sites.…”
mentioning
confidence: 99%
“…However, a major limitation of CT is cumulative ionizing radiation associated with repeated CT exams, which are often needed to monitor the development of lesions in longitudinal studies. On the other hand, although lung MRI has been more challenging compared to other MR exams due to the presence of air, respiratory/cardiac motion, and the short normalT2* of the lung parenchyma, remarkable technological advances have been achieved during the past years to address these challenges, and multiple studies have demonstrated convincing imaging performance of lung MRI with appropriate scan times . However, one of the main challenges of conventional MRI using Cartesian acquisitions is the sensitivity to motion (ie, heart beating or respiration) and the requirement of breath‐holds in clinical routine.…”
mentioning
confidence: 99%
“…When using power injectors this technique is particularly helpful for visualizing perfusion defects when pursuing subtraction images (Fig. 6 d and 7 c) [ 147 , 148 ].…”
Section: Magnetic Resonance Angiographymentioning
confidence: 99%